Odpowiedzi

Najlepsza Odpowiedź!
2010-03-06T16:13:18+01:00
3√2+5√2-12√2/(1+√2)=
-4√2/1+√2= górę i dół mnożymy przez 1-√2
-4√2+4×2/1-2=
-4√2+8/-1
/ -kreska ułamkowa
2010-03-06T16:16:10+01:00
2010-03-06T16:18:30+01:00
√18+√50-2√72 (1-√2) √18-√36+√50-√100-2√72+2√144
= ----------------- *------ = -------------------------------------- =
(1+√2) (1-√2) 1-2

√9*2-6+√25*2-10-2√36*2+2*12 3√2-6+5√2-10-2*6√2+24
= ---------------------------------- = ---------------------------- =
-1 -1
3√2-6+5√2-10-12√2+24 -4√2+8
= ---------------------------- = ---------- = 4√2 -8
-1 -1


Liczę na naj :P